(3TQM GdJSgjd aj GdfMh dGHf eGdcs - (3CKjQ GdOjf CHi MjGf eMeO Hf jhSa Hf Ydj Hf MjGf GdfaQis; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH (B" (3PcQ CHfjI GdCaYGd (B" (3hgh BNQ eG cJHg GdeDda ef TQM GdJSgjd s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
Keywords: (3GdfMhs